1993
DOI: 10.2514/3.11699
|View full text |Cite
|
Sign up to set email alerts
|

Study of supersonic intersection flowfield at modified wing-body junctions

Abstract: The problem of supersonic flow control using fillets and sweep for a wing-body junction has been investigated numerically using a three-dimensional Navier-Stokes code, which employs the MacCormack's time-split finite volume technique. An elliptic grid generation technique with direct control over spacing has been developed for constructing the grid at a filleted wing-body junction. The computed results for pressure distribution, particle paths, and limiting streamlines on the flat plate and fin surface for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The Reynolds-averaged Navier-Stokes solutions obtained by Chen and Hung [19] on a cylinder perpendicular to a flat plate revealed that the main effect of increasing the Mach number is to produce a larger vortex structure because of the shock-wave/boundary-layer interaction. The Navier-Stokes solutions of Lakshmanan and Tiwari [85] showed that, by properly filleting the junction between a swept fin and a flat One application of the study of the flow around a fin perpendicular to a flat wall is the design of wing-fuselage junctions. Favorable aerodynamic interference was achieved between the wing and the fuselage by Pritulo et al [89].…”
Section: Supersonic Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reynolds-averaged Navier-Stokes solutions obtained by Chen and Hung [19] on a cylinder perpendicular to a flat plate revealed that the main effect of increasing the Mach number is to produce a larger vortex structure because of the shock-wave/boundary-layer interaction. The Navier-Stokes solutions of Lakshmanan and Tiwari [85] showed that, by properly filleting the junction between a swept fin and a flat One application of the study of the flow around a fin perpendicular to a flat wall is the design of wing-fuselage junctions. Favorable aerodynamic interference was achieved between the wing and the fuselage by Pritulo et al [89].…”
Section: Supersonic Flowmentioning
confidence: 99%
“…Buning [82], McMaster and Shang [87], Knight et al [83], Chen and Hung [19], Lakshmanan and Tiwari [85,86], and Zemsch and Degrez [94]. Hung and Buning [82] performed an experiment to assess the influence of the thickness of the incoming boundary layer on the hoseshoe vortex forming at the junction.…”
Section: Supersonic Flowmentioning
confidence: 99%